MANAJEMEN KOMUNIKASI PENGASUH DALAM PELAKSANAAN KEGIATAN EKSTRAKULIKULER DIBA’ DI PONDOK PESANTREN PUTRI - Nisa’, Hamidah Salwa Khoirun; Najib, Muhammad; Ahmad, Nur Fatih; Mahfudloh, Ririn Inayatul; Qomaruddin, Qomaruddin (STKIP Pesisir Selatan, 2025)
These activities play a crucial role in shaping the character of students through the regular recitation of shalawat. The success of this program is significantly influenced by the effectiveness of the caregivers' communication in delivering material, engaging students, and overcoming challenges encountered during the process. This research aims to analyze the communication strategies employed by caregivers, identify obstacles faced, and evaluate the contribution of communication to the effectiveness of diba activities. The research adopts a descriptive qualitative approach with a field research method. Data was collected through direct observations, in-depth interviews with caregivers, student leaders, and junior students, as well as documentation of relevant activities. Thematic analysis was employed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that caregivers implement simple verbal communication, positive nonverbal expressions, and a participatory approach through group discussions and the involvement of senior students. The main challenges identified include varying levels of student comprehension, limited time for caregivers to provide guidance, and technical constraints such as inadequate facilities.